2004
DOI: 10.1614/ws-03-068r
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory data analysis to identify factors influencing spatial distributions of weed seed banks

Abstract: Comparing distributions among fields, species, and management practices will help us understand the spatial dynamics of weed seed banks, but analyzing observational data requires nontraditional statistical methods. We used cluster analysis and classification and regression tree analysis (CART) to investigate factors that influence spatial distributions of seed banks. CART is a method for developing predictive models, but it is also used to explain variation in a response variable from a set of possible explana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…In both classification and regression tree models (CART), each split of the target variable (e.g., branches/nodes) uses only the single most influential predictor variable (i.e., that maximizes the homogeneity within the resulting two groups) at each node (Wiles and Brodahl 2004), and this minimizes or eliminates the impact that collinearity among predictor variables can have in global regression models (Breiman et al 1984). Moreover, CART is well-suited to ecological studies involving numerous and diverse kinds of predictor variables because it lacks assumptions about underlying distributions.…”
Section: Discussionmentioning
confidence: 99%
“…In both classification and regression tree models (CART), each split of the target variable (e.g., branches/nodes) uses only the single most influential predictor variable (i.e., that maximizes the homogeneity within the resulting two groups) at each node (Wiles and Brodahl 2004), and this minimizes or eliminates the impact that collinearity among predictor variables can have in global regression models (Breiman et al 1984). Moreover, CART is well-suited to ecological studies involving numerous and diverse kinds of predictor variables because it lacks assumptions about underlying distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Vayssières et al (2000) also found that CART models performed better than multiple logistic regression when modeling three tree species in California. In weed science, CART analyses have been used to identify factors influencing spatial distributions of weed seed banks by Wiles and Brodahl (2004).…”
Section: Methodsmentioning
confidence: 99%
“…The CART method, however, is not a panacea for every data-mining challenge. Both strong and weak points of referred method are summarized in Table 9 (Yarus et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…CART has been applied in several areas, such as the financial industry (Cashin and Dattagupta 2008), manufacturing and marketing (Chen and Su 2008), and medical industries (Snousy et al 2011), and even in weed science (Wiles and Brodahl 2004). Different versions of decision trees have also been applied in the petroleum industry to estimate production profiles along with uncertainty assessments in long-term production forecasts (Jensen 1998); for data classification and partitioning to predict permeability from well logs (Perez et al 2005); for case-based reasoning and planning of the execution of a fracturing job (Popa and Wood 2011); to predict average production of a well from several variables, such as producer, acid volume, and strength (Yarus et al 2006); and to predict the oil production from five significant parameters (permeability, porosity, first shut-in pressure, residual oil, and water saturation) by use of a neural-based decision-tree model (Lee and Yen 2002). Recently, the boosted regression tree was applied to the data from more than 15,000 producing wells in the Barnett shale play to predict maximum gas rates and find the relative importance of the different inputs used in the treatment (Lafollette et al 2012).…”
Section: Introductionmentioning
confidence: 99%